Zastosowanie metody boosting w indukcji reguł - Kubus, Mariusz (Boosting Application in Rules Induction, 2008)
The induction of classification rules in the implication form is an alternative to classification trees in a presence of non-metric variables. Many algorithms of rules induction follow the classical manner separate-and-conquer [Michalski 1969], Cohen and Singer [1999] proposed to use boosting instead of the step ''separate " and implemented it in SLIPPER. The goal of this paper is to test the selected properties of SLIPPER algorithm and compare it with popular CART.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 470-477